Pengaruh Inventory Intensity, Capital Intensity, Concentrated Ownership, dan Institutional Ownership terhadap Tax Avoidance pada Perusahaan Manufaktur BEI 2021-2023 - Adrian Maulana, Moch; Anggraini Aripratiwi, Ratna; Shofiatul Jannah, Binti; Aristantia, Selvia Eka (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This study aims to analyze the effect of inventory intensity, capital intensity, concentrated ownership, and institutional ownership on tax avoidance. The reason is due to the phenomenon of a very significant decrease in tax revenue from the manufacturing sector in the past year. Quantitative type, the population studied was IDX manufacturing companies in 2021-2023. The sample was determined through purposive sampling and amounted to 258 samples. Using multiple linear regression with the SPSS 25 application. The research resulted in a positive effect of inventory intensity, capital intensity, and concentrated ownership on tax avoidance. While institutional ownership does not affect tax avoidance. The results of this study can be utilized by companies and governments in addressing tax avoidance in their respective perspectives.